IMPROVED RATIO OF GERAM RESTRICTIONS AND REDUCTION OF PAHAT PAID WITH MODIFIED WEARS OF PAVING CUTS AT DVA MACHINE - Didik Nurhadiyanto; Mujiyono Mujiyono (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2005)
This research is aimed to determine the differences of chipcompression ratio and tool wear between a modified double cuttingtool and a standard cutting tool.The workpiece is made of VCN 150 with a dimension of e 1,75 inchand 200 mm long. Because the diameter of the blank is constant, the spindle rotation is set to 265 RPM Both cutters use the same coolant and have the same cutting angle. The properties to be varied are depth of cuts and feed Depth of cuts of standard cutting tool is formulated by the blank diameter substituted by the final diameter and than divided by two. The same formulation goes for depth of cuts of modified cutting tool. Tool wears and chip compression ratio values chosen is the biggest value on each cutting edge. Steps of this research one: Record the tool wear and chip compression ratio for each feed, which one 0,043; 0,066; 0,0875; and 0,/75 mmlrev while using depth of cuts of 0,5; I; 1,5 and 2 mm. Each treatment is done 5 times or each cutting stroke and the average is taken as a result. Comparing tool wear and chip compression ratio resulted from the utilization of modified cutting tool and standard tool.It can be concluded from the result of this research that (I) using modified cutting tool, there is an improvement of chip compression ratio equal to 6,74% compared to the standard cutter (2) using modified cutting tool there is a reduction tool wear equals to 14,53% compared the standard cutting /001.